CENSURERENDE KONTEKSTER: At finde en virtuel samlings værdi - Cleal, Bryan (Tidsskriftet Antropologi, 2001)
This article sets out to exploit the leeway that is allowed, perhaps encouraged, by the notion of collection. The article proposes that collections are apprehended in relation to the connections/relationships that underpin them. One understands these connections by invoking context but, due to the subject matter of the article, this is also seen to be problematic. The article focuses specifically on research being conducted on a EU funded Information Technology project. The aim of this project is to develop web-based tools to facilitate work in film archives. The collection with which the article is concerned is not, though, those held in the archives but, rather, the collection of individuals, institutions and resources that have been drawn together to work on this project. Against this background the article discusses the nature of the work being conducted and the problems that have been encountered in realising the vision that drives the research forward. In the conclusion the term virtual collection is cast in another light, which looks less to technology and more to the social and material conditions under which collections both acquire and communicate value.